WebSphere Application Server-Express : a development example for new developers - Moore, Bill (IBM redbooks., 2003)
This IBM Redbooks publication is a practical guide to developing Web applications using WebSphere Studio. WebSphere Studio is used to develop a sample Web application targeted to the WebSphere Application Server - Express runtime platform. It implements a sample scenario based on realistic requirements for small and medium customers, and provides an end-to-end guide for the development of this scenario. The book focuses on describing a simple process that allows non technical readers to understand and participate in the development of Web applications using WebSphere Studio . Part 1 of the book is an overview of the Web application development process and the tools available within WebSphere Studio. Part 2 describes the requirements and design of a sample application and details the process, architecture, and tools used to develop that sample. It is a detailed explanation of the steps needed to build the sample application. This illustrates how to achieve areas of functionality commonly found in dynamic Web applications, and provides worked examples that new developers can use in their own applications. Please note that the additional material referenced in the text is not available from IBM.